STRATEGI PEMASARAN SYARIAH DALAM MENINGKATKAN PENJUALAN KERUPUK PEYEK UNIANG PADANG LUAR - Eli Febriani; Ulva Della Rosa; Rayzul Hawari (Jurnal Ekonomi dan Bisnis, 2024)
This research is motivated by the lack of marketing strategies, namely in terms of workforce or human resources, promotion, and place to market it. This is the aim of this research to analyze and implement effective and efficient sharia marketing strategies to increase sales of Uniang Padang Luar peyek crackers. From the results of research conducted on the Uniang Padang Luar peyek cracker business, it can be stated that the sharia marketing strategy in increasing sales is to increase effective ways to create products with halal ingredients in order to increase consumer interest, improve the taste of peyek crackers by using ingredients new and halal raw materials in accordance with sharia business principles, maintaining low prices and not excessively taking profits in accordance with sharia selling price principles, maintaining consumer loyalty by using new and halal raw materials in accordance with sharia so that consumers are not disappointed, maintaining promotions by honest way in accordance with sharia business principles so as not to harm other parties, maintaining price discounts for customers who buy in large quantities in accordance with sharia business principles, improving product quality and good service to maintain customer loyalty in accordance with sharia business principles, maintaining Characteristics of crackers so that they are in great demand by consumers, especially Muslims, maintain good relations with customers and maintain the location where crackers are sold so that they can be reached by many people in accordance with sharia business principles, and maintain and improve service and maintain good relations with consumers in accordance with sharia business principles.